A Systematic Study of Interference Effects in Non-Sequential Double Ionisation. (August 2015) - Maxwell, Andrew S; de Morisson Faria, Carla Figueira
Synopsis: We perform a detailed study of interference in time-delayed NSDI showing significant effects on the momentum dependent transition amplitude. We also provide analytical arguments to back up our findings.